2018
DOI: 10.1002/rrq.218
|View full text |Cite
|
Sign up to set email alerts
|

How Well Can Students Evaluate Online Science Information? Contributions of Prior Knowledge, Gender, Socioeconomic Status, and Offline Reading Ability

Abstract: A B S T R A C TThis study investigated how well seventh-grade students (n = 1,434) evaluated the credibility of online information in science. The analysis examined the extent to which evaluation appeared to share aspects of other elements of online research and comprehension, including locating, synthesizing, and communicating. This study also investigated the extent to which prior knowledge, gender, socioeconomic status, and offline reading ability affected students' evaluation during online reading in scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 17 publications
2
28
1
2
Order By: Relevance
“…A final interesting issue in literacy research is gender-related differences. Several studies showed an advantage for girls in reading fluency and reading comprehension (Logan and Johnston, 2009, 2010; Torppa et al, 2018) and similar patterns have also been observed in other studies on Online Reading Comprehension (Forzani, 2016; Salmerón et al, 2018; Kanniainen et al, 2019). McKenna et al (2012) reported that middle school girls have more positive reading attitudes toward reading print texts for recreational as well as academic purposes, while their attitudes toward reading digital texts are better for academic purposes, but not for recreational purposes.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…A final interesting issue in literacy research is gender-related differences. Several studies showed an advantage for girls in reading fluency and reading comprehension (Logan and Johnston, 2009, 2010; Torppa et al, 2018) and similar patterns have also been observed in other studies on Online Reading Comprehension (Forzani, 2016; Salmerón et al, 2018; Kanniainen et al, 2019). McKenna et al (2012) reported that middle school girls have more positive reading attitudes toward reading print texts for recreational as well as academic purposes, while their attitudes toward reading digital texts are better for academic purposes, but not for recreational purposes.…”
Section: Introductionsupporting
confidence: 82%
“…Similarly, in a study on Singapore secondary school students (Wu, 2004), male students performed better in graph reading, female students in graph construction, whereas no gender differences were found in graph interpretation and evaluation. While a general advantage for males in online reading performance cannot be documented due to the very little difference found in our sample (with marginal statistical significance), it can rather certainly be excluded that a general advantage for females (described for instance by Kanniainen et al, 2019 or Forzani, 2016) can be found in the Italian school system when accessing and using digital information. This, following Jang and Ryoo’s (2018) suggestions, might reflect a less positive attitude toward digital media in Italian girls, even for academic purposes (different, in this case, from both North-European and Asian female students).…”
Section: Discussioncontrasting
confidence: 60%
“…When students are required to locate sources for a class assignment, they need to decide what counts as good or reliable sources and whether the information in those sources are to be trusted (e.g., Forzani, 2018). Such determinations require epistemic knowledge, which is knowledge of what qualifies as trustworthy or credible and whether there is sufficient evidence or justification to support claims or conclusions (Alexander & Disciplined Reading and Learning Research Laboratory, 2012; Kuhn & Park, 2005).…”
Section: Centering Diverse Forms Of Knowledgementioning
confidence: 99%
“…Second, as we noted in the previous subsection, studies in psychology and communications have demonstrated that cognitive biases and other irrational factors often detract from one's ability to evaluate credibility rigorously. Furthermore, in the literacy field, scholars have correlated background knowledge, topic interest, and motivation with reading comprehension (e.g., Baldwin, Peleg‐Bruckner, & McClintock, ; Recht & Leslie, ; see also Forzani, ); it is possible that such factors also impact one's ability to evaluate credibility. Although controlled experiments have provided insights into how individuals interact with information online, such research cannot account for individual motivation, biases, prior knowledge, identity, and a myriad of other complex factors at play in the real world.…”
Section: Literature Reviewmentioning
confidence: 99%